Dopamine, cognitive function, and gamma oscillations: role of D4 receptors - Furth, Katrina E.; Mastwal, Surjeet; Wang, Kuan H.; Buonanno, Andres; Vullhorst, Detlef (Frontiers in Cellular Neuroscience, 2013)
Cognitive deficits in individuals with schizophrenia and close relatives are considered core symptoms of this disorder, and can manifest at the prodromal stage. Antipsychotics ameliorate positive symptoms but only modestly improve cognitive symptoms. The lack of treatments that improve cognitive abilities currently represents a major obstacle in developing more effective therapeutic strategies for this debilitating disorder. While D4 receptor-specific antagonists are ineffective in the treatment of positive symptoms, animal studies suggest that D4 receptor drugs can improve cognitive deficits. Moreover, recent work from our group suggests that D4 receptors synergize with the neuregulin/ErbB4 signaling pathway, genetically identified as risk factors for schizophrenia, in parvalbumin-expressing interneurons to modulate gamma oscillations. These high-frequency network oscillations correlate with attention and increase during cognitive tasks in healthy subjects but to a much lesser extent in affected individuals. This finding, along with other observations indicating impaired GABAergic function, has lead to the idea that abnormal neural activity in the prefrontal cortex in individuals with schizophrenia reflects a perturbation in excitation/inhibition balance. Here we review the current state of knowledge of D4 receptor functions in the prefrontal cortex and hippocampus, two major brain areas implicated in schizophrenia. Special emphasis is given to studies focusing on the potential role of D4 receptors in modulating GABAergic transmission and to an emerging concept of a close synergistic relationship between dopamine/D4R and neuregulin/ErbB4 signaling pathways that tunes the activity of PV interneurons to regulate gamma frequency network oscillations and potentially cognitive processes.